2014
DOI: 10.1111/gwmr.12085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seasonal Factors on Petroleum Hydrocarbon Vapor Biodegradation and Intrusion Potential in a Cold Climate

Abstract: A detailed seasonal study of soil vapor intrusion at a cold climate site with average yearly temperature of 1.9 °C was conducted at a house with a crawlspace that overlay a shallow dissolved‐phase petroleum hydrocarbon (gasoline) plume in North Battleford, Saskatchewan, Canada. This research was conducted primarily to assess if winter conditions, including snow/frost cover, and cold soil temperatures, influence aerobic biodegradation of petroleum vapors in soil and the potential for vapor intrusion. Continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Based on the evidences provided by the above-mentioned empirical studies, U.S.EPA (2015a) suggested that additional investigation may be not necessary when the source to building vertical separation distance is greater than 1.8 m (6 ft) for dissolved contamination or 4.6 m (15 ft) for light non-aqueous phase liquid (LNAPL). Furthermore, results from numerical (Hers et al, 2000;Abreu and Johnson, 2006;Abreu et al, 2009;Knight and Davis, 2013;Hers et al, 2014) and analytical models (DeVaull, 2007;Yao et al, 2014;Verginelli and Baciocchi, 2014;Yao et al, 2016) were consistent with the empirical exclusion distance values reported above, showing that, in nearly all cases, a source to building vertical separation distance greater than 2 m or 5 m is sufficient to attenuate to acceptable risk-based levels petroleum hydrocarbon vapors from dissolved-phase or LNAPL sources, respectively.…”
Section: Introductionsupporting
confidence: 79%
“…Based on the evidences provided by the above-mentioned empirical studies, U.S.EPA (2015a) suggested that additional investigation may be not necessary when the source to building vertical separation distance is greater than 1.8 m (6 ft) for dissolved contamination or 4.6 m (15 ft) for light non-aqueous phase liquid (LNAPL). Furthermore, results from numerical (Hers et al, 2000;Abreu and Johnson, 2006;Abreu et al, 2009;Knight and Davis, 2013;Hers et al, 2014) and analytical models (DeVaull, 2007;Yao et al, 2014;Verginelli and Baciocchi, 2014;Yao et al, 2016) were consistent with the empirical exclusion distance values reported above, showing that, in nearly all cases, a source to building vertical separation distance greater than 2 m or 5 m is sufficient to attenuate to acceptable risk-based levels petroleum hydrocarbon vapors from dissolved-phase or LNAPL sources, respectively.…”
Section: Introductionsupporting
confidence: 79%
“…It is well known that microorganisms can oxidize petroleum hydrocarbons to carbon dioxide while utilizing electron acceptors such as molecular oxygen [8, 9]. Unlike recalcitrant compounds such as chlorinated solvents, a large number of petroleum hydrocarbon are susceptible to aerobic biodegradation at rates that are quite rapid with respect to rates of physical transport by diffusion and advection [2122], leading to vapors attenuation by several orders of magnitude within a few meters [2, 1018]. Based on this, U.S. EPA and ITRC guidances [6,7] proposed vertical screening distances (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The water table was found to be between 2.5 and 2.9 m bgs [1547.2-1546.8 m elevation] for the contaminated core, and taking into account water table fluctuations and the capillary fringe, zone III is largely either saturated or characterized by high moisture content (e.g., in the capillary fringe). High moisture content generally results in reduced oxygen levels (Hers et al 2014). These factors may explain why observed microbial communities in zone III were distinct from those observed in zone II.…”
Section: Discussionmentioning
confidence: 93%